Hierarchical multimodal attention for end-to-end audio-visual scene-aware dialogue response generation. (September 2020) - Le, Hung; Sahoo, Doyen; Chen, Nancy F.; Hoi, Steven C.H.
Highlights: Hierarchical attention, including question self-attention and question-guided attention on input helps to improve the model performance. Features of multiple modalities can be fused through nonlinear approaches for better contextual representations. Input video length, question types in user queries, and turn positions affect the quality of the generated responses. Abstract: This work is extended from our participation in the 7 th Dialogue System Technology Challenge (DSTC7), where we participated in the Audio Visual Scene-aware Dialogue System (AVSD) track. The AVSD track evaluates how dialogue systems understand video scenes and responds to users about the video visual and audio content. We propose a hierarchical attention approach on user queries, video caption, audio and visual features that contribute to improved evaluation results. We also apply a nonlinear feature fusion approach to combine the visual and audio features for better knowledge representation. Our proposed model shows superior performance in terms of both objective evaluation and human rating as compared to the baselines. In this extended work, we also provide a more extensive review of the related work, conduct additional experiments with word-level and context-level pretrained embeddings, and investigate different qualitative aspects of the generated responses.